2014
DOI: 10.2478/intox-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitive effect of curcumin on thyroid cancer cell death induced by radioiodine-131

Abstract: Curcumin is a natural product widely consumed by humans. It has many biological properties. In this study, we investigated the radiosensitive effect of curcumin on thyroid cancer cells against cellular toxicity induced by 131-I. Human thyroid cancer and human non-malignant fibroblast cells (HFFF2) were treated with 131-I and/or curcumin at different concentrations (5, 10 and 25 µg/ml) for 48 h. The cell proliferation was measured by determination of the surviving cells by using MTT assay. Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…5 Curcumin could selectively sensitize thyroid cancer cells to death induced by radioactive iodine without any toxicity on nonmalignant fibroblast cells. 13 In the present study, we showed that curcumin significantly protected human healthy lymphocytes from genotoxicity induced by external IR. These results showed curcumin has a radioprotective effect on normal cells and a radiosensitizing effect on cancer cells, and so is promising for use as a natural agent in cancer therapy.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…5 Curcumin could selectively sensitize thyroid cancer cells to death induced by radioactive iodine without any toxicity on nonmalignant fibroblast cells. 13 In the present study, we showed that curcumin significantly protected human healthy lymphocytes from genotoxicity induced by external IR. These results showed curcumin has a radioprotective effect on normal cells and a radiosensitizing effect on cancer cells, and so is promising for use as a natural agent in cancer therapy.…”
Section: Discussionsupporting
confidence: 54%
“…The curcumin concentrations were selected based on previous studies. 5,13 Piperine concentration was selected based on previous studies that showed P has a IC 50 of 61 µg/mL on the HeLa cell line 14 and it did not exhibit any genotoxicity or cellular toxicity up to 60 µM (17 µg/mL). 15 Control samples were treated with diluted DMSO in RPMI at the same concentration as the other curcumin and/or piperine samples.…”
Section: Blood Treatmentmentioning
confidence: 99%
“…Several studies demonstrated that antioxidants have radioprotective effects on normal cells by mainly decreases ROS levels while these compounds have radiosensitive effects in tumor cells by increasing ROS levels. Curcumin as a powerful antioxidant has radioprotective effect on normal cells [30], while it has radiosensitizing effect in tumor cells by increasing ROS level and suppressing inflammatory process such as NF-κΒ activation pathway induced by ionizing radiation [31][32][33]. Genestein has antioxidant activity and protect healthy cell against toxicity induced by IR [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently we showed that curcumin had protective effect against genotoxicity induced by iodine radioactive in human lymphocyte 5 . Curcumin could sensitize selectively thyroid cancer cell to death induced by iodine radioactive without any toxicity on non-malignant fibroblast cells 13 . In the present study, we showed that curcumin significantly protected human healthy lymphocyte against genotoxicity induced by external IR.…”
Section: Discussionmentioning
confidence: 99%
“…The twelve samples groups are following: control, ionizing radiation (IR), 5 µg/ml CUR+IR, 10 µg/ml CUR+IR, 25 µg/ml CUR+IR, 5 µg/ml CUR+2.5 µg/ml(P)+IR, 10 µg/ml CUR+2.5 µg/ml(P)+IR, 25 µg/ml CUR+2.5 µg/ml(P)+IR, 2.5 µg/ml(P)+IR, 25 µg/ml CUR, 2.5 µg/ml(P), 5 µg/ml CUR+2.5 µg/ml(P). The curcumin concentrations were selected based on previous studies 5, 13 . Piperine concertation was selected based on previous studies that P has a IC50 61 µg/ml on HeLa cell line 14 and it did not exhibited any genotoxicity and cellular toxicity up to 60 µM (17 µg/ml) 15 .…”
Section: Blood Treatmentmentioning
confidence: 99%